Landrace maize seed selection method for small producers - Oliveira, Jocimeri Portes de; Martins, Leonardo Alves; Azevedo, Letícia Fátima de (Revista de Ciências Agroveterinárias, 2023)
The selection of seeds with physiological quality is essential for small farmers, who select and save seeds for the next crop. The objective of this work was to evaluate the physiological quality of seeds in three positions on the ear of two varieties landrace maize. The experiment was carried out in the municipality of Bagé, in the year 2020, with seeds from the 2019/2020 harvest at Faculdade IDEAU. Seeds of the Ferrinho and Amarelão varieties were used, in a completely randomized design, with four replications and the treatments were composed by separating the seeds in three positions of the ear: Basal, Intermediate and Apical. Tests for germination, first germination count, seedling length and seedling dry mass were performed. The seeds of the Basal and Intermediate positions present germination between 94 and 98%, higher than the Apical position. The first germination count and the tests of seedling length and dry mass showed a low level of vigor for all treatments. The seeds of the Basal and Intermediate positions of var. of Crioulo Amarelão and Ferrinho corn showed higher viability than the seeds from the apical position of the ear. However, both showed a low level of vigor, indicating that cultivation techniques need to be improved to generate seeds with a high level of vigour.